Book Review: Himanshu, India Inequality Report 2018: Widening Gaps. Issue 2 (August 2018) - Acharya, Sarthi
Himanshu, India Inequality Report 2018: Widening Gaps . New Delhi: Oxfam India, 2018, 82 pp. Available athttps://www.oxfamindia.org/sites/default/files/WideningGaps_IndiaInequalityReport2018.pdf